La comunicación familiar para prevenir situaciones de riesgo por abuso sexual, en los niños del sexto grado paralelo D de la Unidad Educativa Alonso de Mercadillo, periodo 2020-2021. - Benítez Zhunio, Liliana del Cisne (2022)
The investigative work entitled; Family communication to prevent risk situations due to sexual abuse, in children of the sixth grade parallel D of the Unidad Educativa Alonso de Mercadillo, period 2020-2021, aimed to investigate family communication to prevent risk situations due to sexual abuse, it was a mixed research (quali-quantitative), descriptive, non-experimental design and cross-sectional, the survey on family communication and the Prudencia Luzoro test were applied to a sample of 26 students. The results found in relation to the first objective analyzed qualitatively are based on the survey responses; they do not have good communication due to lack of trust, due to the age of those investigated compared to older siblings, the absence of parents due to work, very strict attitudes with physical and verbal punishment, or they do not live with parents; Regarding the Luzoro Prudence test, it was evidenced that 92% they are easily fooled by known people, 65% of children have not clear that their body belongs to them and nobody can touch them, 77% of children investigated do not recognize between good secrets and bad secrets, 38% of children investigated are confused by this type of bad caresses, given that they are received by people close to them and 62% of children do not receive information because they believe that talking about sexuality is a taboo. Therefore, the investigation concludes that there is a lack of assertive communication, with aggressive and permissive parenting attitudes; Likewise, it is evident that the population investigated due to their limited knowledge faces risk situations such as deception, abuse of their body, because they are confusing bad caresses with good ones, for this reason, the guide "Kiko's rule" is presented as a strategy prevention psychoeducational. Palabras claves: family communication, risk prevention, risk situations, sexual abuse